Stream-keys generation based on graph labeling for strengthening Vigenere encryption - Antonius Cahya Prihandoko; Dafik Dafik; Ika Hesti Agustin (Institute of Advanced Engineering and Science, 2022)
This paper address the cryptographic keys management problem: how to generate the cryptographic keys and apply them to secure encryption. The purpose of this research was to study on utilizing graph labeling for generating stream-keys and implementing the keys for strengthening Vigenere encryption. To achieve this objective, the research was carried out in four stages: developing an algorithm for generating stream-keys, testing the randomness of the constructed keys, implementing the eligible keys in a modified Vigenere encryption and, finally, analyzing the security of the encryption. As the result, most of stream-keys produced by the algorithm are random, and the implementation of the stream keys to the modified Vigenere cipher achieve good security. The contributions of this research are utilizing graph labeling to generate stream-keys and providing different encryption keys for different blocks in a block based cipher with low storage capacity. The novel technical results yielded from this research are the algorithm of developing the source of the stream-keys based on graph labeling, the algorithm of constructing the initial block keys, and the protocol of a modified Vigenere encryption using stream-keys and operated in cipher block chaining mode.